2020
DOI: 10.1049/iet-epa.2019.0498
|View full text |Cite
|
Sign up to set email alerts
|

Compact designs of permanent‐magnet biased fault current limiters

Abstract: This study proposes two novel compact designs of three-phase permanent-magnet biased fault current limiters (PMFCLs), namely, delta-shaped and compact cross delta PMFCLs. The actual representation of neodymium permanent magnet (PM) is based on the Jiles-Atherton modelling for the demagnetisation behaviour in the second quadrant of its actual non-linear B-H hysteresis loop. This PM is a preliminary representation validated through experimental measurements to ensure the trends and behaviour of PMFCL during its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Some of the common electrical parameters for the proposed delta-shaped PMFCLs are shown in Table 1. The design arrangement of four AC coils and five NdFeB-N42 PM segments (4AC-5PM) three-phase delta-shaped PMFCL (Eladawy et al 2020) is shown in Fig. 2(a).…”
Section: Design Topologymentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the common electrical parameters for the proposed delta-shaped PMFCLs are shown in Table 1. The design arrangement of four AC coils and five NdFeB-N42 PM segments (4AC-5PM) three-phase delta-shaped PMFCL (Eladawy et al 2020) is shown in Fig. 2(a).…”
Section: Design Topologymentioning
confidence: 99%
“…2(a). The subdivided coils of each phase are connected in series, with differential connection (Eladawy et al 2020), to carry the line current of the protected power line. The uniformly distributed PM segments are sandwiched and arranged between the two soft magnet triangles throughout the delta-shaped design.…”
Section: Design Topologymentioning
confidence: 99%
See 3 more Smart Citations